2014
DOI: 10.20460/jgsm.2014815644
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Integration Mechanisms in Open Innovation Projects: The Case of Interorganizational Networks

Abstract: In recent years, there has been a tendency to evolve the innovation process into a flexible model known as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, the results of hypothesis 2 open innovation significantly affect the company's performance, according to the research carried out by Brown et al, 2014;Greco et al, 2020. The focus on open innovation aims to facilitate the management of internal and external sources of information or knowledge that can be used to develop innovation within the company. A business's interaction with many innovation channels may be detrimental since this may reduce the firm's efficacy in putting innovative ideas into action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the results of hypothesis 2 open innovation significantly affect the company's performance, according to the research carried out by Brown et al, 2014;Greco et al, 2020. The focus on open innovation aims to facilitate the management of internal and external sources of information or knowledge that can be used to develop innovation within the company. A business's interaction with many innovation channels may be detrimental since this may reduce the firm's efficacy in putting innovative ideas into action.…”
Section: Discussionmentioning
confidence: 99%
“…Nnamsh 2019 says that open innovation means that companies increasingly use superficial knowledge to accelerate their internal innovation processes (Umoh et al, 2019). Several studies found a relatively robust analysis of the effect of open innovation on company performance (Brown et al, 2014;Greco et al, 2020). Based on the results of the research described, this study can formulate the second hypothesis: H2: Open innovation has an impact on firm performance.…”
Section: The Relationship Between Open Innovation and Company Perform...mentioning
confidence: 90%